Pengaruh Pemberian Rebusan Daun Salam (Eugenia polyantha Wight.) Terhadap Kadar Kolesterol Low Density Lipoprotein (LDL) Serum Tikus Putih (Rattus norvegicus) Hiperkolesterolemia - Afrilliani, Dyah Ari; Supriyanta, Bambang; Rahayu, Muji (POLTEKKES KEMENKES YOGYAKARTA, 2014)
High levels of LDL cholesterol can lead to heart disease because of clogging and hardening of the arteries. One of the medicinal plants that can reduce levels of LDL cholesterol in the blood is a bay leaf. The content of flavonoids and tannins in the bay leaves serves to lower levels of fat and cholesterol in the blood. This study aims to determine the effect of decoction of bay leaves (Eugenia polyantha Wight.) to the decrease LDL cholesterol level in mice (Rattus norvegicus) with hypercholesterolemia. This study is purely experimental research with Pre and Post Test With Control Group Design, using 25 white rats as experimental animals were divided into five groups, which are the positive control group, three treatment groups and the comparison group. LDL cholesterol levels were measured by the method of Precipitation Reagent For In Vitro Determination of LDL cholesterol with the CHOD-PAP by photometric systems. Data were analyzed descriptively and statistically using One Way ANOVA test and t-test independent sample. Descriptive analysis found the percentage of the decrease of serum LDL cholesterol levels in mice of hypercholesterolemia at doses 0.18 gram/200 gram of weight was 25.96%, at dosess 0.27gram/200 gram of weight was 23:45%, and at doses 0.36 gram/200 gram of weight was 35.94%. Results of One Way ANOVA test showed a significance of 0.000 which means there is the effect of decoction of bay leaves to the decrease of LDL cholesterol levels in mice with hypercholesterolemia. T-test results found that the decoction of bay leaves at doses 0.36 gram/200 gram of weight lowers LDL cholesterol levels were comparable with administration of simvastatin at doses 0.18 mg/200 gram of weight (P > 0.05).The conclusion of this research was the decoction of bay leaves may lower serum LDL cholesterol levels in hypercholesterolemic mice with percentage of 25.96% at doses 0.18 gram/200 gram of weight, 23:45% at doses 0.27 gram/200 gram of weight, and 35.94% at doses 0.36 gram/200 gram of weight. The decoction of bay leaves at doses 0.36 gram/200 gram of weight may lower LDL cholesterol levels which comparable with administration of simvastatin at doses 0.18 mg/200 gram of weight (p > 0.05).